(untitled) (Asian Journal of Social Science Studies, 2022)
The legalization of same-sex marriage in China remains unlikely to be achieved. Some same-sex couples have begun to use legal guardianship as a way to obtain some of the rights of marriage. Even if the assigned guardianship system grants some marriage privileges, it denies same-sex couples access to social aid, protection from domestic violence, a reduced mortgage, and communal property, among other things. In this paper, I analyze and evaluate the Civil Code of the People‟s Republic of China and conduct interviews with a lesbian couple and a gay couple who have previously applied for assigned guardianship to determine how the assigned guardianship system in China prevents same-sex couples from attaining full sexual citizenship.